Numerical simulation of a cable-stayed bridge response to blast loads, Part I: Model development and response calculations - Tang, E.; Hao, Hong (Pergamon, 2010)
Many researchers have conducted comprehensive experimental and numerical investigations to examine civilian structures' response to explosive loads. Most of the studies reported in the literature deal with building structures and structure components. Studies of bridge structures subjected to blast loads are limited. This study performs numerical simulations of dynamic responses of a large cable-stayed bridge under explosive loadings. All numerical simulations are carried out using the LS-DYNA explicit finite element code. This paper describes the bridge under consideration, blast load estimation, finite element model, material model, and detailed numerical simulation results of the bridge to blast loads from a 1000 kg TNT equivalent explosion at 0.5 m from the bridge tower and pier, and 1.0 m above the deck. Damage mechanism and severity of the bridge tower, pier and deck are examined. The companion paper Hao and Tang (2010) [19] presents intensive numerical simulation results of the bridge components under blast loads of different scaled distances, progressive collapse analyses of the bridge after either one of the four main bridge components is damaged, and the safe scaled distance for bridge protection before initiating catastrophic collapse. The effectiveness of FRP strengthening of bridge concrete back span for blast load resistance is also investigated.